Analisis Tingkat Pengetahuan Berdasarkan Keluhan Pekerja Terhadap Gangguan Gerak Otot Kerangka (Gotrak) Pada UD. Radalla Collection - Sugiantoro, Sugiantoro; Sunaryo, Merry; Sunaryani , Rosita Putri; Nurani , Ilmi Tri; Reynaldi , Ivan Alvian (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Occupational Safety and Health (K3) is very important for all workers and company owners to prevent occupational accidents and occupational diseases (PAK). UD. Radalla Collection, which manufactures screen printing and children's clothing, involves repeated use of the hands in a long sitting position, which increases the risk of PAK such as musculoskeletal disorders. Socialization is needed to educate craftsmen about the dangers and risks of ergonomics. Previously, a subjective survey had been conducted to identify complaints of Musculoskeletal Disorders (MSDs). From the observation results, it was found that workers did not know about skeletal muscle movement disorders, so workers worked carelessly. UD workers. The Radalla Collection is expected to increase awareness and understanding of the importance of preventing skeletal muscle disorders (gotrak) to avoid accidents and occupational diseases.